«Doktor Zhivago» and Leonid Pasternak - Ivanova, Natalya (Slavica, 2021)
In this article, we analyze the transformation of values in the literature and art of the first half of the 20th century through the creative strategies of two closely linked people: the poet Boris Pasternak and his father, the painter Leonid Pasternak. An academician of painting, Leonid Pasternak renewed the traditions of realism, being in close contact with Leo Tolstoy while working on the illustrations for Tolstoy’s novel “The Resurrection”. Having made a creative journey from the movement of “peredvizhniki” (“the Itinerants”) toward Impressionism, he did not accept the newest trends, as opposed to his son who had undergone a long period of fascination with Futurism, as well as the influence of Modernism. This conflict of aesthetics lost its poignancy with the passing of the years and with the geographical distance (Pasternak the father having emigrated in the beginning of the 20s). Thus, Boris Pasternak returned to the poetics of the classical Russian prose in his novel “Doctor Zhivago.” But the Christian values on which the conceptual basis of the novel rests, remained unknown to the father, who had passed away just before his son began working on the novel. The result was the novel itself with its covert subtextual influence and the polemics of the son and the father, the poet and the artist.